ANALYSIS OF PUBLIC EXPENDITURES IN SUPPORT OF AGRICULTURE DEVELOPMENT IN ALBANIA - Eneida Thomaj (European Scientific Journal, ESJ, 2015)
Albania is considered an advantegous country for agriculture (possesing a rich land and water resources), but still its contribution to national GDP is relatively low compared to other sectors, thus implying a low relevance given from the government. This paper tries to analyse the budgetary expenditures in support to agriculture sector in Albania and its aim is to provide a preliminary assessment of these expenditures. For this reason, a first analysis of actual agriculture conditions is realized, related also to reforms undertaken from the government in agriculture support. Furthermore, trends are observed regarding budget funds allocated to agriculture in total and also in terms of composition (six main programmes are analyzed such as planification and management, food safety, rural development etc.). Some key parameters analyzed in the case of Albania are then compared to EU budget practices to reach a comparison with best practices and to signal some directions as where the budget expenditures could move to. This paper gives some conclusions on actions to be taken from the government in increasing efficiency and optimizing agriculture production (not only on the agriculture funds allocation but also on the level of public information access – on budget drafting and realization; advice offered to farm holders and better transparency on steps to follow in benefiting from concessional financing).